Pengaruh Perencanaan Pajak Dan Aktiva Pajak Tangguhan Terhadap Financial Performance: Studi Kasus Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2022 - Parluhutan, Taufik Akbar (Journal Economy and Currency Study (JECS), 2023)
This study intends to carry out an analysis related to the influence of tax planning variables and deferred tax assets variables on financial performance. The targets of this research are food and beverage sub-sector manufacturing companies that have been registered on the IDX from 2019 to 2022. Then the sampling method used in this study was purposive sampling and 9 samples of companies were obtained. While researchers used three data analysis methods, namely the classical assumption test, multiple linear regression test and hypothesis testing. The results shown in this study are that the tax planning variable has no partial effect on financial performance, but deferred tax assets have a partial effect on financial performance. While simultaneously the variable tax planning and deferred tax asset variables jointly have an influence on financial performance.